Lichens growing on painted metal plates - García, Renato (2015)
This study was based on the description of different species of lichens which were growing on metal plates exposed to the weather conditions in La Plata, Buenos Aires Province, Argentina. Among the six species observed, Caloplaca cinnabarina was the most common. Lichen species were identified by observation under optical microscope and chemical reactions. The chemical composition of the paint was analyzed by IRS and the metal composition of the plates by SEM and EDS. SEM analysis also revealed paint cracking around the lichen and paint particles trapped in the thallus.